SCHOOL LITERACY MOVEMENT PROGRAM IN STRENGTHENING ANTI-BULLYING CHARACTER OF MOVING SCHOOL STUDENTS - Simorangkir, Melda Rumia Rosmery; Tjalla, Awaluddin; Badrujaman, Aip (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This research supports the teacher professionalism competency approach in handling bullying cases by implementing a school literacy movement program. The research method uses a qualitative approach, with data collection techniques through interviews, observation and document review which are then analyzed using the CIPP method. Research findings show that the school literacy movement is effective in creating a reading culture in the secondary school environment and is able to reduce cases of bullying. Teachers are actively involved in inserting literacy elements in various subjects to improve students' reading and writing skills. In addition, giving research projects or assignments that involve the analysis of reading material has a big impact on students who form discussion groups or anti-bullying clubs with a focus on positive values and personal development.